Konflik dan Integrasi, Sebuah Kajian Awal: Kasus Kerusuhan Medan, April 1994 - Legowo, Wijaya K. (UI Scholars Hub, 2012)
Problems of integration cannot be separated from conflicts. They are two sides of the same coin. A long, escalating conflict may contribute to disintegration. Schermerhorn (1978) on his valuable book mentions there are three models of integration: first, the harmony of the cultural problems; second, the conflict between subordination of an ethnic group and the superordinates, and third, problems of legitimacy. We have found many ethnic conflicts in the Indonesia’s plural society, especially the Chinese ethnic. The Indonesian Chinese minorities of Jakarta are still traumatized by and frightened of their memories for the Medan Riots (1994), the May Riots (1998) and the NTT incidents (2012), all of which are caused by the hatred feelings of majority towards the Indonesian Chinese ethnic. Since the New Order Era, in order to come up with those problems, the government had issued numerous sets of regulations; however they had not fostered harmony of the ethnic relations within such plural society, particularly between the Indonesian Chinese ethnic and indigenous peoples in numerous regions. Based on the microscopic research on the Medan Riots, I have found a certain model problem of conflicts and integration : a certain relation between the Chinese ethnic and the bureaucracy has become one of the factors keeping the legitimation of conflicts.